Deluging Thrombosis: An Unusual Presentation of Acute Promyelocytic Leukemia - Jandial, Aditya; Mishra, Kundan; Lad, Deepesh; Naseem, Shano; Malhotra, Pankaj (Indian Journal of Medical and Paediatric Oncology, 2020)
Acute promyelocytic leukemia (APML) patients are prone to thrombosis. However, thrombosis at presentation is rare in APML. Our patient presented with thrombosis and cytopenia, and the clinical diagnosis was of paroxysmal nocturnal hemoglobinuria. However, subsequent peripheral blood smear and bone marrow study confirmed the diagnosis of APML. The patient was successfully managed with anticoagulation, arsenic trioxide, and all-trans retinoic acid.
Keywords: Acute promyelocytic leukemia; anti-coagulation; chemotherapy; thrombosis